COMMUNITY PURCHASING MOTIVATION TOWARD LOCAL FOOD PRODUCTS: A QUALITATIVE STUDY USING NVIVO IN BARRU REGENCY - M. Rasda; Ratnawati; Mukmin Muhammad (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal